Gandhian Perspective of Development - Kemi Anthony Emina (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
We are living in an age in which the major concerns of people are Facebook, WhatsApp, e-mail, e-commerce, sensex, gross domestic product, markets, dividends, globalisation, horse-trade politics, and such other aspects of commerce, economics, development, and politics. In such a stage, where does the value-based development, purity of means and ends, production by the masses instead of mass production, truth, non-violence, non-possession, gender equality, austerity in life, etc. preached by our Father of the Nation, Mahatma Gandhi, stand? The world has changed drastically in its inner and outer spheres; the life rhythm has turned totally in its core. In such a time, the ideals of Gandhian teaching seem ‘utopian’ and superficial to the new-gen, high-tech civilised individuals and groups. This work contains a detailed study of the prevalent development strategies and their drawbacks and lapses that make the situation more aggravating. It also analyses the Gandhian prescriptions for development and their significance in the modern world.